2018
DOI: 10.1111/his.13468
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mesothelioma in situ

Abstract: These cases show that morphologically bland single-layered surface mesothelial proliferations with molecular alterations seen previously only in invasive malignant mesotheliomas exist, and presumably represent malignant MIS. More cases are need to understand the frequency of such changes and the time-course over which invasive tumour develops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 15 publications
1
55
0
Order By: Relevance
“…All the different truncated and mutated forms of cytoplasmic BAP1 tested thus far have been biologically inactive . Because benign cells always show BAP1 nuclear staining, the absence of BAP1 nuclear staining is a specific and reliable marker to distinguish mesothelioma from benign atypical mesothelial hyperplasia at its earliest stages of development . Overall, approximately 70% of epithelial and 50% of sarcomatoid mesotheliomas contain somatic BAP1 mutations, resulting in an absence of BAP1 nuclear staining .…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%
“…All the different truncated and mutated forms of cytoplasmic BAP1 tested thus far have been biologically inactive . Because benign cells always show BAP1 nuclear staining, the absence of BAP1 nuclear staining is a specific and reliable marker to distinguish mesothelioma from benign atypical mesothelial hyperplasia at its earliest stages of development . Overall, approximately 70% of epithelial and 50% of sarcomatoid mesotheliomas contain somatic BAP1 mutations, resulting in an absence of BAP1 nuclear staining .…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%
“…1,15 Nonetheless, MIS remained controversial until recently, due to lack of agreement on the cell of origin in mesothelioma, lack of clear and uniform diagnostic criteria, difficulty with interpretation because of similarities with benign mesothelial hyperplasia, and the belief of some that MIS was not a premalignant lesion but instead surface spread of concurrent invasive disease not present in that particular biopsy (even if radiology was normal). 7,16,17 Recently, advances in molecular techniques have resulted in renewed interest in the concept, recognising its potential for early diagnosis in some patients. We have reported loss of BRCA1-associated protein-1 (BAP1) in some effusions and biopsies of patients without invasive tumour at the time who developed invasive tumour later.…”
Section: Introductionmentioning
confidence: 99%
“…18 Preliminary data from Churg et al have identified molecular alterations of BAP1 and CDKN2A in MIS, both of which have been implicated in the pathogenesis of MM. 16,19 Additionally, the same group studied expression of methylthioadenosine phosphorylase (MTAP) in MIS. MTAP has been suggested as an alternative for CDKN2A as a diagnostic marker for MM in surgical and cytology samples as it is frequently co-deleted owing to their close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, the in situ stage of mesothelioma has recently been a focus of great interest for understanding the progression of this disease. 8,9 Mesothelioma in situ is associated with a high risk of developing invasive mesothelioma. However, the progression to invasive disease typically occurs over a relatively prolonged period of time, making timely curable interventions possible.…”
Section: Introductionmentioning
confidence: 99%